2015
DOI: 10.1097/md.0000000000001083
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Reporting Quality of Randomized Controlled Trials in 3 Leading Diabetes Journals From 2011 to 2013 Following CONSORT Statement

Abstract: Supplemental digital content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
3
11
1
1
Order By: Relevance
“…The level of compliance varies depending on the CONSORT checklist item with information on participant flow through the study having the highest compliance; however, many checklist items had compliance less than 50%. Similar findings have been reported in current literature across multiple fields—diabetes journals, surgery journals, otorhinolaryngologic journals, and the Korean Journal of Anesthesiology . Our results suggest that compliance has actually decreased since the introduction of CONSORT to TRANSFUSION in checklist items such as blinding and method to generate the random allocation sequence.…”
supporting
confidence: 87%
“…The level of compliance varies depending on the CONSORT checklist item with information on participant flow through the study having the highest compliance; however, many checklist items had compliance less than 50%. Similar findings have been reported in current literature across multiple fields—diabetes journals, surgery journals, otorhinolaryngologic journals, and the Korean Journal of Anesthesiology . Our results suggest that compliance has actually decreased since the introduction of CONSORT to TRANSFUSION in checklist items such as blinding and method to generate the random allocation sequence.…”
supporting
confidence: 87%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30] But most have focused on small numbers of trials or specific diseases, journals, or time periods. These studies used various criteria for their assessments, which were frequently not defined.…”
Section: Introductionmentioning
confidence: 99%
“…A large systematic review updated in 2012 showed that, despite improvements in the completeness of reporting for 22 of 25 CONSORT checklist items, there are still major reporting deficiencies in some areas [5]. Subsequent reviews and research have confirmed that reporting remains suboptimal in areas such as sample size calculations and consistency between prespecified and reported outcomes [6][7][8][9]. Adherence to the CONSORT statement for Abstracts is also variable and incomplete [10].…”
Section: Introductionmentioning
confidence: 99%